2013
DOI: 10.1124/dmd.113.053405
|View full text |Cite
|
Sign up to set email alerts
|

The Letrozole Phase 1 Metabolite Carbinol as a Novel Probe Drug for UGT2B7

Abstract: Carbinol [4,49-(hydroxymethylene)dibenzonitrile] is the main phase 1 metabolite of letrozole, a nonsteroidal aromatase inhibitor used for endocrine therapy in postmenopausal breast cancer. We elucidated the contribution of UDP-glucuronosyltransferase (UGT) isoforms on the glucuronidation of carbinol. Identification of UGT isoforms was performed using a panel of recombinant human UGT enzymes. Kinetic studies were done in recombinant human UGT2B7 and pooled human liver microsomes (HLMs). A liquid chromatography-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The inhibitory potency ( K i , 10.0 µM) of AM-2201 on UGT2B7-catalyzed naloxone 3′-glucuronidation was similar to that ( K i, 9.8 μM) of cannabidiol for UGT2B7-catalyzed ethanol glucuronidation [ 30 ], suggesting that AM-2201 may cause drug interactions with UGT2B7 substrates, such as morphine, zidovudine, efavirenz, ethanol, carbinol, JWH-018, and flurbiprofen [ 30 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory potency ( K i , 10.0 µM) of AM-2201 on UGT2B7-catalyzed naloxone 3′-glucuronidation was similar to that ( K i, 9.8 μM) of cannabidiol for UGT2B7-catalyzed ethanol glucuronidation [ 30 ], suggesting that AM-2201 may cause drug interactions with UGT2B7 substrates, such as morphine, zidovudine, efavirenz, ethanol, carbinol, JWH-018, and flurbiprofen [ 30 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carbinol, the major phase I metabolite of letrozole, has been demonstrated to be a novel in vitro probe substrate for UGT2B7, with high selectivity, high affinity, and high conversion rate in vitro (Table S6, Supporting Information). Notably, it also has a potential as an in vivo probe for clinical studies, because physiologic activity of carbinol is strongly reduced compared with letrozole . Denopamine, one of the oral β1‐adrenoceptor selective partial agonists, has been reported to be regioselectively glucuronidated by UGT2B7 in HLM and HIM.…”
Section: Non‐fluorescent Probes For Human Ugtsmentioning
confidence: 99%
“…Notably, it also has a potential as an in vivo probe for clinical studies, because physiologic activity of carbinol is strongly reduced compared with letrozole. [135] Denopamine, one of the oral β1-adrenoceptor selective partial agonists, has been reported to be regioselectively glucuronidated www.advancedsciencenews.com www.biotechnology-journal.com by UGT2B7 in HLM and HIM. Notably, the glucuronidation site of denopamine in human is the alcoholic hydroxyl group, but not the phenolic group.…”
Section: Probes For Ugt2b7mentioning
confidence: 99%
“…In vitro studies have demonstrated that CYP3A4 and CYP2A6 are involved in the metabolism of letrozole, converting it to carbinol (25,26). Carbinol is then conjugated by glucuronyl transferase, more precisely by the UGT2B7 isoform ( Figure 2) (27). The drug has a high affinity for CYP2A6 and a low affinity for CYP3A4.…”
Section: Pharmacokineticsmentioning
confidence: 99%